Broadband γ-graphyne saturable absorber for Q-switched solid-state laser. (30th October 2019) - Yang, Qi; Zhang, Xiaoyan; Yang, Zixin; Ren, Xianghe; Wang, Jun; Li, Qiaodan; Cui, Xiaoli; Zhu, Xiaolei
Abstract: γ -graphyne, a two-dimensional carbon material, has attracted much attention due to its unique characteristics, such as high carrier mobility and high stability. In the present study, a γ -graphyne saturable absorber (SA) was fabricated and characterized. The linear optical absorption in the spectral range from the visible to mid-infrared as well as the nonlinear optical character of the SA were investigated. Passively Q-switched solid-state lasers emitting at 639 nm, 1342 nm and 1932 nm were realized using the γ -graphyne SA. The results indicate that γ -graphyne could be a promising alternative to the rare broadband optical modulator.